Removal of basic dyes from aqueous solutions using coconut hard shell powder as a sorbent - Pathak J.; Rupainwar D.C.; Talat M.; Hasan S.H. (My University, 2025)
The potentiality of sorbent coconut hard shell powder (CHSP) has been investigated as an effective sorbent to removal of malachite green and crystal violet from aqueous solutions. The maximum removal of malachite green and crystal violet have been found at pH 10.5 and 10.2, initial dyes concentration 5 mg L-1 and temperature 30°C, respectively. The effects of different parameters such as contact-time, particle diameter of the sorbent, dyes concentration, pH of the solution and temperature have been investigated.